2000
DOI: 10.3109/s101650070036
|View full text |Cite
|
Sign up to set email alerts
|

Factors correlated with emotional instability in SLE outpatients

Abstract: Eighty-four female outpatients with systemic lupus erythematosus (SLE) who are able to live on their own were investigated. We statistically analyzed the relationship between emotional instability based on psychological tests (Cornell Medical Index), and physical, medical, and social factors based on both our clinical records and original questionnaires. The emotional instability was related to not "working," an older "age at the time of SLE diagnosis," being "anxious about the adverse effects of steroids," or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Actually, some studies using another psychological scale have suggested that personality or psychological dysfunction might modulate disease outcomes such as disease activity and organ damage 7 , 9 - 11 , 14 ) . However, there is an opposite result in Japan: Ishikura has reported that disease activity might not be correlated with a psychological feature such as emotional instability among outpatients 23 ) . There is a possibility that serious diseases may lead to change in personality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, some studies using another psychological scale have suggested that personality or psychological dysfunction might modulate disease outcomes such as disease activity and organ damage 7 , 9 - 11 , 14 ) . However, there is an opposite result in Japan: Ishikura has reported that disease activity might not be correlated with a psychological feature such as emotional instability among outpatients 23 ) . There is a possibility that serious diseases may lead to change in personality.…”
Section: Discussionmentioning
confidence: 99%
“…However, most previous findings were from western countries. In Japan, few studies have been conducted [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation